Repeated Winning and Losing Experiences in Chronic Social Conflicts Are Linked to RNA Editing Pattern Difference - Fu-Xia Ru (Frontiers in Psychiatry, 2022)
Winner-loser effects influence subsequent agonistic interactions between conspecifics. Previous winning experiences could strengthen future aggression and increase the chance of winning the next agonistic interaction, while previous losing experiences could have the opposite effect. Although the role of A-to-I RNA editing has been recently implicated in chronic social defeat stress and aggressive behavior, it remains to be further elucidated in chronic social conflicts in agonistic interactions, especially in the repeated aggression (winners) and repeated defeat (losers) resulted from these conflicts. In the current study, transcriptome-wide A-to-I RNA editing in the dorsal striatum was investigated in a mouse model of chronic social conflicts, and compared between mice repeatedly winning and losing daily agonistic interactions. Our analysis identified 622 A-to-I RNA editing sites in the mouse dorsal striatum, with 23 to be differentially edited in 22 genes, most of which had been previously associated with neurological, psychiatric, or immune disorders. Among these differential RNA editing (DRE) sites four missense variants were observed in neuroligin 2 (Nlgn2), Cdc42 guanine nucleotide exchange factor 9 (Arhgef9) BLCAP apoptosis inducing factor (Blcap), and cytoplasmic FMR1 interacting protein 2 (Cyfip2), as well as two noncoding RNA sites in small nucleolar RNA host gene 11 (Snhg11) and the maternally expressed 3 (Meg3) gene. Moreover, significant changes were observed in gene functions and pathways enriched by genes with A-to-I RNA editing in losers and especially winners compared to controls. Our results demonstrate that repeated winning and losing experiences in chronic social conflicts are linked to A-to-I RNA editing pattern difference, underlining its role in the molecular mechanism of agonistic interactions between conspecifics.